Influence of Parental Attitudes on Formation of Psychological Resilience and Adherence to Medical Regime in Adolescents after Liver or Renal Transplantation - Marta Biernacka; Anna Jakubowska-Winecka; Piotr Kaliciński (MDPI AG, 2021)
Identifying the causes of poor disease control and medication non-adherence is indispensable so that patients can benefit from treatment. The aim of our study was to determine the relationship between parental attitudes, the development of psychological resilience, and systematic medication adherence in a group of adolescents after kidney and liver transplantation. The analysis included the results obtained from 96 families. A total of 52 patients after kidney transplantation and 44 patients after liver transplantation, aged 12-18 years and their parents were examined. The types of parental attitudes were assessed using the Parental Attitude Scale. The patient's resilience was determined with the Resiliency Assessment Scale. The MMAS-8 was used to assess the regularity of medication-taking behavior. A total of 61% of the patients in the study group displayed high levels of psychological resilience. The analyses showed a positive correlation between resilience and the systematic taking of medication by the patients. Moreover, it was found that the analyzed link between psychological resilience on the degree of the regularity of medication intake was enhanced by a specific type of parental attitude. The obtained results confirm the importance of psychological resources in developing better disease control. The relationship between the type of parental attitudes and medication adherence indicates the need to take into account the family context during the child's treatment.